Anatomy of the frontal gland and ultramorphology of the frontal tube in the soldier caste of species of Nasutitermitinae (Isoptera, Termitidae) - Santos, Conceicao A.; Costa-Leonard, Ana M. (Wiley-Blackwell, 2006)
is a predominant characteristic, conditioned by the presence of castes with different morphology, ontogeny, and development. The soldier caste is unique among social insects and it is responsible for colony defense. Soldiers belonging to the Nasutitermitinae subfamily are very peculiar, since they may be polymorphic and present a nasus in addition to either developed or vestigial mandibles. The defensive secretions of soldiers of the neotropical Nasutitermitinae have been the aim of several chemical studies, but few data exist concerning the anatomy and histology of the exocrine glands. This article presents a comparative study on the anatomy of the frontal gland of soldiers of several Nasutitermitinae species: Syntermes dirus (Burmeister), Syntermes nanus (Constantino), Constrictotermes cyphergaster (Silvestri), Nasutitermes corniger (Motschulsky) and Velocitermes heteropterus (Silvestri), with emphasis on the ultramorphology and ultrastructure of the frontal tube.
Keywords: termites; exocrine gland; defense; nasute; morphology